2021
DOI: 10.3390/medicina57121344
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Different Exercise Interventions to Improve Gait Speed in Older Adults after Acute Coronary Syndrome

Abstract: Background and Objectives: The world’s population is rapidly aging, and it is estimated that, by 2050, every sixth person on earth will be older than 65 years. Around 30% of older adults entering cardiac rehabilitation (CR) meet the criteria of frailty. Frailty identification has not been included in the routine evaluation of CR patients yet, and there is a lack of evidence on what training regimen for improving physical performance in frail people is optimal. Therefore, the aim of our study was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A detailed list of types of surgeries has been provided in Supplemental Digital Content 1, http://links.lww.com/EJA/A916. The exclusion criteria were patients with a history of alcohol abuse, dementia or prior neurosurgery procedures; patients with significant cognitive impairment [as determined by the Chinese version of Mini-Mental State Examination (MMSE) score of 17 or lower] 13,14 ; patients admitted to the ICU; and patients whose surgery ended at 8 p.m. or later 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed list of types of surgeries has been provided in Supplemental Digital Content 1, http://links.lww.com/EJA/A916. The exclusion criteria were patients with a history of alcohol abuse, dementia or prior neurosurgery procedures; patients with significant cognitive impairment [as determined by the Chinese version of Mini-Mental State Examination (MMSE) score of 17 or lower] 13,14 ; patients admitted to the ICU; and patients whose surgery ended at 8 p.m. or later 15 …”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were patients with a history of alcohol abuse, dementia or prior neurosurgery procedures; patients with significant cognitive impairment [as determined by the Chinese version of Mini-Mental State Examination (MMSE) score of 17 or lower] 13,14 ; patients admitted to the ICU; and patients whose surgery ended at 8 p.m. or later. 15 Pre-operative and intra-operative data collection Prior to the scheduled surgical procedures, trained research assistants conducted a 60-min baseline assessment in the patient wards to collect demographic data. The demographic characteristics of the participants, such as age, sex, BMI, comorbidities and prehospital medications, were documented.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Cardiac rehabilitation could promote the physical and mental health of older persons, improving their quality of life [7,8] , and offer bene ts for older CHD patients, such as reduced mortality and rehospitalization rates and further revascularization [9,10] . Many studies have reported that aerobic exercise training improves exercise capacity, frailty, and quality of life in older CHD patients [11][12][13][14] . However, the patients included in these previous studies were relatively young compared with those in the current study.…”
Section: Signi Cant Clinical Bene Ts Of Exercise Rehabilitation For O...mentioning
confidence: 99%
“…www.nature.com/scientificreports/ rehabilitation could promote the physical and mental health of older persons, improving their quality of life [14][15][16][17] , and offer benefits for older CHD patients, such as reduced mortality and rehospitalization rates and further revascularization 18,19 . Many studies have reported that aerobic exercise training improves exercise capacity, frailty, and quality of life in older CHD patients [20][21][22][23] . However, the patients included in these previous studies were relatively young compared with those in the current study.…”
Section: Significant Clinical Benefits Of Exercise Rehabilitation For...mentioning
confidence: 99%